Kemampuan Daya Ledak Otot Tungkai dan Kecepatan pada Kegiatan Ektrakurikuler Pemain Bolavoli Unpari - Suparman, Suparman; Suhdy, Muhammad; Sovensi, Ever (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the level of leg muscle explosive power and speed of Unpari volleyball players in 2025. This is a quantitative descriptive study with a single variable, without comparisons or linking to other variables. The population of this study was 20, and the sample was 20 players who actively participated in training activities at Unpari in 2025 using a total sampling technique. The instruments used in this study were the Vertical Jump Test to measure leg muscle explosive power and the 30-meter sprint test to measure speed. The results of this study indicate that: 1) The leg muscle explosive power of Unpari volleyball players in 2025 averaged 115.18, categorized as Good. 2) The speed ability of Unpari volleyball players in 2025 averaged 4.28, categorized as Good. Keywords: Volleyball, Leg Muscle Explosive Power, Speed